2009
DOI: 10.5539/elt.v2n4p51
|View full text |Cite
|
Sign up to set email alerts
|

ESL Students’ Attitude towards Texts and Teaching Methods Used in Literature Classes

Abstract: Malaysia's Vision is for the country to become a fully developed nation by 2020. In order to compete at international level, the country needs to produce future workers who are well-versed in English. The National Philosophy of Education aims to produce holistic graduates who excel academically and have better intercultural understanding, which resulted in the re-introduction of literature into the curriculum. In addition, English is also used as the medium of instruction for teaching science and mathematics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 8 publications
4
53
1
1
Order By: Relevance
“…These studies in the Arabic context often identified a mixed attitude toward literature in Arabic-speaking communities. However, scholars outside the Arab world (Tehan, Yuksel, & Inan, 2015;Babaee & Yahya, 2014;Lakshmi & Jayachandran, 2012;Paesani, 2011;Fogal, 2010;Ghazali et al, 2009;Ögeyik, 2007) have recently and vehemently highlighted the role of literature in language learning and teaching. Literature occupies a central place in language learning.…”
Section: Related Studies In the Arab World And Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies in the Arabic context often identified a mixed attitude toward literature in Arabic-speaking communities. However, scholars outside the Arab world (Tehan, Yuksel, & Inan, 2015;Babaee & Yahya, 2014;Lakshmi & Jayachandran, 2012;Paesani, 2011;Fogal, 2010;Ghazali et al, 2009;Ögeyik, 2007) have recently and vehemently highlighted the role of literature in language learning and teaching. Literature occupies a central place in language learning.…”
Section: Related Studies In the Arab World And Beyondmentioning
confidence: 99%
“…The results indicate that learners at an advanced level feel comfortable analyzing literature when material is presented in a teacher-centered manner and this material improves their meta-cognitive awareness, thereby helping students become more actively involved in the process of learning the target language. Ghazali et al (2009) studied the attitudes of school students toward literary materials in Malaysian schools. Mixed methods data from 110 class five students defined different aspects that motivate learners to develop a positive attitude toward L2 learning.…”
Section: Related Studies In the Arab World And Beyondmentioning
confidence: 99%
“…Due to that, students do not fully understand what they have learned and do not know how to appreciate literature accordingly (Aziz & Nasharudin, 2010). In fact, a study done by Ghazali, Setia, Muthusamy & Jusoff (2009) revealed that teachers spent a lot of time discussing plot, characters, theme, setting and moral values of the texts in class and the students responded that the teaching strategies used were boring. That is worrying as students seem to lose focus in learning Literature as a result of teaching methods applied by the teachers.…”
Section: Introductionmentioning
confidence: 99%
“…7, No. 9;2014 academic articles that are relevant to their interest and journal writing using the story mapping strategy could help improving students' attitude toward reading and writing as Ghazali (2009) stated that students' attitude is essential in maintaining their success in language learning.…”
Section: Literature Reviewmentioning
confidence: 99%